Faktor Fundamental Keuangan Terhadap Harga Saham di Perusahaan Makanan dan Minuman yang Terdaftar di BEI 2015-2019 - Januar Eky Pambudi; Hendra Galuh Febrianto; Dhea Zatira (Universitas Muhammadiyah Tangerang, 2022)
Investments in the form of stocks actually have a high risk in accordance with the investment principle, namely low risk low return, high risk high return. An investor should really understand about stock prices and often conduct stock price analysis first so as not to make the wrong investment because the price movement of a stock cannot be predicted with certainty. The purpose of this study was to determine the effect of financial fundamentals on stock prices in food and beverage companies listed on the Indonesia Stock Exchange 2015-2019. The results of data analysis partially show that the Debt to Equity Ratio (DER) has no and no significant effect on stock prices. The results of data analysis partially show that Net Profit Margin (NPM) has a negative and significant effect on stock prices. The results of data analysis partially show that Earning Per Share (EPS) has an effect and is significant on stock prices. The results of simultaneous data analysis show that the independent variables Debt to Equity Ratio (DER), Net Profit Margin (NPM) and Earning Per Share (EPS) have a simultaneous and significant effect on the dependent variable of stock prices.